STAT3 modulates the DNA damage response pathway - Barry, Seán P (Blackwell Publishing Ltd, 2010)
The STAT3 transcription factor is well known to function as an anti-apoptotic factor, especially in numerous malignancies. Recently we showed that STAT3 is cytoprotective and that cells lacking STAT3 are more sensitive to oxidative stress. A key feature of oxidative stress involves activation of the DNA damage pathway. However, a role for STAT3 or its contribution in response to DNA damage has not been described. In the present study we show that cells lacking STAT3 are less efficient in repairing damaged DNA. Moreover, STAT3 deficient cells show reduced activity of the ATM-Chk2 and ATR-Chk1 pathways, both important pathways in sensing DNA damage. Finally we show that MDC1, a regulator of the ATM-Chk2 pathway and facilitator of the DNA damage response, is modulated by STAT3 at the transcriptional level. These findings demonstrate that STAT3 is necessary for efficient repair of damaged DNA, partly by modulating the ATM-Chk2 and ATR-Chk1 pathways.